Dye aggregation in layer-by-layer dyeing of cotton fabrics. Issue 24 (18th February 2016) - Khan, Farzana; Liu, Panpan; Xu, Fujun; Ma, Ying; Qiu, Yiping
Abstract : This work utilizes layer-by-layer (LbL) assembly technique to dye cotton fabrics and investigates the dye aggregation in these polymer matrixes. Abstract : This work presents the dye aggregation behaviors in layer-by-layer (LbL) dyed cotton fabrics. Fluorescein isothiocyanate labeled poly(allylamine hydrochloride) (PAH-FITC) was LbL-assembled on cotton with poly(acrylic acid) (PAA) or alone. The obtained (PAA/PAH-FITC)* n and (PAH-FITC)* n films demonstrated that the LbL-assembly technique is suitable for homogenously dyeing the complex fabrics. Importantly, different aggregation behaviors of dye FITC were exhibited in the two matrixes of (PAA/PAH-FITC)* n and (PAH-FITC)* n, showing the significant role of LbL-assembly in textile dyeing. Moreover, for the deposition of PAH-FITC, the LbL assembly of PAH-FITC is superior to the continuous immersion of cotton fabric in PAH-FITC solution in terms of the deposition amount, presenting a unique advantage of LbL-assembly in textile dyeing.